Use of medial upper arm free flap in oral cavity reconstruction: a preliminary study. Issue 5 (May 2018) - Saenthaveesuk, P.; Zhang, S.-e.; Zheng, G.-s.; Liang, Y.-j.; Su, Y.-x.; Liao, G.-q.
Abstract: The medial upper arm has previously been proposed as a potential free flap donor site, but the clinical application of such flaps in head and neck reconstruction has not been popular. The preliminary results of the clinical application of medial upper arm free flaps in oral cavity reconstruction are reported here. Five patients with oral cancer underwent surgical resection and neck dissection, with simultaneous reconstruction using a medial upper arm free flap. Functional outcomes were investigated using the University of Washington Quality of Life Questionnaire. Sensory-motor functions of the upper arm donor site were recorded before and after surgery. Four flaps were successfully transferred. One flap was abandoned during surgery because of a lack of perforators, and a forearm flap was used instead. All patients survived without loco-regional recurrence or distant metastasis. Functional outcomes, especially swallowing and speech, were satisfactory. The donor site scar was well hidden, with no functional impairment. This initial experience shows that the medial upper arm free flap represents an alternative perforator flap for oral cavity microsurgical reconstruction. The well-hidden scar and better texture match compared with other flaps make it suitable for oral cavity reconstruction.